(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
In order to ensure the continuity of education, the stages of organization of continuous mathematical training, taking into account the specialty, were considered, the plan of continuous mathematical training was analyzed.